ORIENTASI POLITIK ISLAM ERA MADINAH - Alya Syabrina; Ahmad Zulfikri (CV. Denasya Smart Publisher, 2025)
The political orientation of the Medina period was marked by the establishment of the first Islamic political and social order by the Prophet Muhammad SAW who migrated from Mecca in 622 AD. The Prophet Muhammad, who was based in Medina, drafted the Medina Charter which led to Medina. The constitution for this period regulated interreligious and inter-ethnic relations and guaranteed their rights. This political system prioritized national unity through ukhuwah Islamiyah, decision-making (shura), and the application of Islamic law. In addition, Medina became the center of government responsible for social welfare, such as distributing zakat and forming an army to protect the community. This comprehensive, fair and systematic policy became the foundation for the expansion of Islamic influence into the surrounding area. The political orientation of the Medina period became an early model of Islamic governance, integrating spiritual, social, legal and economic dimensions into one. The relationship between Islam and the state in Indonesia is a crucial issue in the history of Islamic.